TANGGUNG JAWAB KEPOLISIAN DALAM PENGAMANAN BENDA SITAAN SEBAGAI BARANG BUKTI DALAM PENYIDIKAN PERKARA TINDAK PIDANA (STUDI KASUS DI POLRESTA MATARAM) - B.Farhana Kurnia Lestari; Jauhari Dewi Kusuma; Gatot Pramedi (Jurnal Ilmiah Hospitality, 2022)
The confiscation of evidence or confiscation is carried out by law enforcement officers for the level of examination, especially for investigation purposes in terms of sufficient evidence, and Responsibility as law enforcement officers in securing confiscated objects. Investigators cannot arbitrarily seize goods without following the rules outlined by laws and regulations. They must comply with the provisions of the Criminal Procedure Code because this is closely related to the dignity of a person guaranteed by the State, government, law, and every citizen as values. HAM. The purpose of this research is to find out the form of Responsibility of investigators for the evidence confiscated at the Mataram Police and what obstacles are faced by the police in securing confiscated objects as evidence in the investigation of criminal cases at the Mataram Police. This research is empirical legal research, which is legal research conducted by collecting data from primary data or data obtained directly, either through observation or direct interviews. The type of approach used is the statutory approach, the conceptual analysis approach, and the case approach. Legal materials are processed deductively, drawing conclusions from a general problem to a specific one. The results of the study show Responsibility In handling confiscated objects by investigators, the investigators are fully responsible for the seized evidence and are prohibited from being used by anyone sanctions investigators who misuse evidence can be subject to disciplinary punishment in the form of a written warning; delay in attending education for a maximum of 1 (one) year; postponement of periodic salary increases; maximum promotion delay 1 (one year; emotional mutations; release from office; placement in a special place for a maximum of 21 (twenty-one) days. The investigator is fully responsible for confiscating evidence and prohibited from being used by anyone. The sanction for the investigator who misuses the evidence may be subject to disciplinary punishment in the form of a written warning; delay in attending education for a maximum of 1 (one) year; postponement of periodic salary increases; postponement of promotion for a maximum of 1 (one) year; emotional mutations; release from office; placement in a special place for a maximum of 21 (twenty-one) days. Coordination to determine the proper storage place for confiscated objects. Small-sized items will be stored in the sub locker. Mataram City Police evidence unit. The obstacles faced in the storage of evidence are the absence of adequate unique and permanent facilities in the form of a room or warehouse that can use for storage of evidence at the Mataram City Police, the lack of maximum supervision of the evidence, either from investigators or from other existing personnel. At the Mataram City Police, individuals still use evidence for personal gain.